Social Capital and the State : Complementarity and Substitution - Narayan, Deepa, 1952- 1952- (The World Bank, 1999)
August 1999 - Whatever their nature, interventions to reduce poverty should be designed not only to have an immediate impact on poverty, but also to foster a rich network of cross-cutting ties within society and between society's formal and informal institutions. Using the lens of social capital - especially bridging or cross-cutting ties that cut across social groups and between social groups and government - provides new insights into policy design. Solidarity within social groups creates ties (bonding social capital) that bring people and resources together. In unequal societies, ties that cut across groups (bridging social capital) are essential for social cohesion and for poverty reduction. The nature of interaction between state and society is characterized as complementarity and substitution. When states are functional, the informal and formal work well together - for example, government support for community-based development. When states become dysfunctional, the informal institutions become a substitute and are reduced to serving a defensive or survival function. To move toward economic and social well-being, states must support inclusive development. Investments in the organizational capacity of the poor are critical. Interventions are also required to foster bridging ties across social groups - ethnic, religious, caste, or racial groups.